2011
DOI: 10.1002/gcc.20918
|View full text |Cite
|
Sign up to set email alerts
|

The seminoma cell line TCam‐2 is sensitive to HDAC inhibitor depsipeptide but tolerates various other chemotherapeutic drugs and loss of NANOG expression

Abstract: Seminomas and embryonal carcinomas (EC) are both type II germ cell tumor (GCT) entities and develop from the same precursor lesion (carcinoma-in situ, CIS). However, they show significant differences in growth behavior, differentiation potential, and gene expression. Although ECs are prone to differentiate into all three germ layers and give rise to the non-seminomatous GCT entities teratoma, choriocarcinoma, and yolk-sac tumor, differentiation of seminomas to these entities is only rarely observed. This might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 31 publications
(39 reference statements)
2
35
0
Order By: Relevance
“…SOX2 was partly methylated in TCam-2, in line with findings illustrating that TCam-2 can differentiate and become SOX2 positive after extra-gonadal injection in mice [54]. A 220 bp region directly upstream of the TSS of SOX2 (chr3:181429712) has previously been shown to be completely hypomethylated in TCam-2 [55]. This is in line with our findings as a consistently hypomethylated region (chr3:181429233-181430485) is shown directly upstream of the TSS while a 652 bp long DMR (chr3:181428046-181428697) between NCCIT and TCam-2 is detected by DMRforPairs in a region ca.…”
Section: Resultssupporting
confidence: 84%
“…SOX2 was partly methylated in TCam-2, in line with findings illustrating that TCam-2 can differentiate and become SOX2 positive after extra-gonadal injection in mice [54]. A 220 bp region directly upstream of the TSS of SOX2 (chr3:181429712) has previously been shown to be completely hypomethylated in TCam-2 [55]. This is in line with our findings as a consistently hypomethylated region (chr3:181429233-181430485) is shown directly upstream of the TSS while a 652 bp long DMR (chr3:181428046-181428697) between NCCIT and TCam-2 is detected by DMRforPairs in a region ca.…”
Section: Resultssupporting
confidence: 84%
“…These data are indicative of allelic differential methylation at the H19 DMD, as expected from the monoallelic expression of H19 in AFSC. We next compared the whole genome transcriptome identity of AFSC_VPA with the seminoma cell line TCam-2, 32 which exhibit characteristics of fetal germ cell ( Supplementary Figure S5 ). Results showed that AFSC and TCam-2 cells share 39% transcriptome identity ( Figure 8f ).…”
Section: Resultsmentioning
confidence: 99%
“…siRNA mediated knockdown of TFAP2C in TCam-2 cells was performed as described by [27]. Scrambled and TFAP2C siRNA were obtained from Origene (TFAP2C SR304789, Origene Technologies, Rockville, USA).…”
Section: Methodsmentioning
confidence: 99%